The potential difficulties faced by students in learning mathematics in vocational high schools: comparative study of external and internal factors - Yanti, Ferda; Bayu Nugroho, Purna; Gunawan, Wawan (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study is meant to describe: (a) Difficulty in learning mathematics in eleventh grade, (b) the reasons behind those difficulty faced by the students eleventh grade, (c) Teachers' efforts to overcome the difficulties of learning mathematics in eleventh grade, (d) Large The level of difficulty in learning mathematics experienced by eleventh graders. This type of research is a type of qualitative research. Difficulties experienced by students are difficulty understanding concepts, difficulties in skills, and difficulties in solving problems Data collection methods used were interview and test methods. Research shows that: (1) Difficulty understanding concepts, difficulties in skills, and difficulties in solving problems. (2) The causes of those difficulty in learning comes from social, emotional, and intellectual of students themselves. (3) Teacher's efforts to overcome learning difficulties by holding remedial. (4) The level of learning difficulties of students included in the category is very difficult. It is hoped that the teacher can overcome student learning difficulties. So that students' difficulties in learning mathematics are slightly overcome. Penelitian ini bertujuan untuk mendeskripsikan: (a) Kesulitan belajar matematika di kelas XI, (b) alasan kesulitan yang dihadapi siswa kelas XI, (c) Upaya guru mengatasi kesulitan belajar matematika di kelas XI, (d) Besar Tingkat kesulitan belajar matematika yang dialami siswa kelas XI. Jenis penelitian ini merupakan jenis penelitian kualitatif. Kesulitan yang dialami siswa adalah kesulitan memahami konsep, kesulitan keterampilan, dan kesulitan menyelesaikan masalah. Metode pengumpulan data yang digunakan adalah metode wawancara dan tes. Penelitian menunjukkan bahwa: (1) Kesulitan memahami konsep, kesulitan dalam keterampilan, dan kesulitan dalam memecahkan masalah. (2) Penyebab kesulitan belajar tersebut berasal dari faktor sosial, emosional, dan intelektual siswa itu sendiri. (3) Upaya guru mengatasi kesulitan belajar dengan mengadakan remedial. (4) Tingkat kesulitan belajar siswa termasuk dalam kategori sangat sulit. Diharapkan guru dapat mengatasi kesulitan belajar siswa. Sehingga kesulitan siswa dalam belajar matematika sedikit teratasi.